Quality management and traceability in crop production - Szathmáry, Zsuzsanna; Győri, Zoltán (Acta Agraria Debreceniensis, 2007)
Today, food safety and quality is an everyday issue. Scandals in the food industry drew attention to the role and responsibility of food producers in the food chain. The European Union has set up a new integrated approach towards food safety, to which Hungary as an EU member and export-oriented country has also joined. The new “from farm to fork” principle states that food and feed production cannot be handled separately, as only feed produced from good quality raw materials can ensure safe food products. Another important issue is the traceability of products, allowing for the localization and recall of the defected item. In Hungary, there have been different documentation systems for tracking and tracing products, such as the land register in crop production, animal register in the livestock sector and hygiene registers in the food industry. In order to meet EU requirements, there is a growing number of initiatives to include primary production in the scope of food safety standards. The study introduces and compares the various management systems used in crop production.